Online Education for Undergraduate Nursing Students During COVID_19 in Saudia: Policy Brief - Zboun, Mamoon (Technium Social Sciences Journal, 2021)
Online education is very important during the pandemic of the COVID_19, so all the countries apply the online education to protect the student from infection, in the universities, there are practical and theory courses in the theory courses it is very easy to apply the distance education but in the practical courses it is very difficult to apply the online education, we can use the traditional teaching method in the lab with safety precaution to protect the student from this COVID-19, we mean by the practical courses that is requiring demonstration in the lab by the students, the aim of the current policy is to identify the main advantages of the distance education, we can apply training programs for the student for dealing with the specialized program that depend on the interaction between the students and the teacher.